2007
DOI: 10.1002/cncr.22899
|View full text |Cite
|
Sign up to set email alerts
|

Utility of parametrectomy for early stage cervical cancer treated with radical hysterectomy

Abstract: BACKGROUND. Removal of the parametrial soft tissue is recommended for patients with cervical cancer undergoing radical hysterectomy. Parametrectomy results in significant morbidity. The objective of the study was to determine factors predictive of parametrial tumor spread and to define a subset of patients at low risk for parametrial disease. METHODS. Patients with invasive cervical cancer who underwent radical hysterectomy from 1989–2005 were examined. Analysis was performed to determine factors associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
131
3
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(152 citation statements)
references
References 34 publications
11
131
3
7
Order By: Relevance
“…Wright et al suggested that parametrial tissue infiltration could increase the risk of tumor recurrence and shorten DFS and OS (Wright et al, 2007). Munagala et al found that the number of parametrial invasion was the sole factor that affected OS and DFS, and the 5-year survival of patients with bilateral parametrial invasion was significantly lower than that of patients with unilateral parametrial infiltration (Munagala et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wright et al suggested that parametrial tissue infiltration could increase the risk of tumor recurrence and shorten DFS and OS (Wright et al, 2007). Munagala et al found that the number of parametrial invasion was the sole factor that affected OS and DFS, and the 5-year survival of patients with bilateral parametrial invasion was significantly lower than that of patients with unilateral parametrial infiltration (Munagala et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Annually, it is estimated that 493,000 women worldwide will be diagnosed with cervical cancer and that 273,000 will die from the disease (Wright et al, 2007). In China, there will be about 130,000 new cases of cervical cancer diagnosed and about 30,000 women who will die from the disease every year.…”
Section: Introductionmentioning
confidence: 99%
“…Este valor está dentro del rango reportado por otras investigaciones en poblaciones similares (que son del 2,4 al 10,9% (18,20,21) ). Lo que implica que se podría realizar en forma segura un procedimiento quirúrgico menos radical en un subgrupo de estas pacientes.…”
Section: Discussionunclassified
“…Se encontró que el estado ganglionar linfático pélvico es el predictor independiente más fuerte para presentar CP, conjuntamente con la profundidad de infiltración. Este factor ha sido previamente reportado como un predictor sólido de propagación parametrial (7,18,(21)(22)(23)(24)(25)(26)(27)(28) .…”
Section: Discussionunclassified
See 1 more Smart Citation